y'' + 5y' + 6y = 0
has characteristic equation
r² + 5r + 6 = (r + 2) (r + 3) = 0
with roots at r = -2 and r = -3, hence the differential equation's characteristic solution is
[tex]y(t) = C_1 e^{-2t} + C_2 e^{-3t}[/tex]
Given that y(0) = 1 and y'(0) = 2, we have
[tex]y(t) = C_1 e^{-2t} + C_2 e^{-3t} \implies 1 = C_1 + C_2[/tex]
[tex]y'(t) = -2C_1 e^{-2t} - 3C_2 e^{-3t} \implies 2 = -2C_1 - 3C_2[/tex]
and solving the resulting system of equations yields C₁ = 5 and C₂ = -4.
So the particular solution to the ODE is
[tex]\boxed{y(t) = 5 e^{-2t} - 4 e^{-3t}}[/tex]